ANALYSIS OF THE PHENOMENON OF SOCIAL COMPARISON FOR INSTAGRAM USERS AS A FORM OF SELF-CONFIDENCE (International Conference on Social and Islamic Studies, 2022)
Self-confidence is very important in our daily lives. When we have confidence we can interact with the environment around us. If someone wants to be happy then they must need high self-confidence so as not to be underestimated by others and show skills in the form of works on social media, one of which is Instagram. Therefore, with the existence of social media, they are competing to show their confidence through Instagram with good photos. But according to the survey results, late adolescents (18 - 21 years old) experienced decreased Self Confidence and conducted Social comparisons with other individuals. Social Comparison is a phenomenon that has an impact on human Self Confidence. The phenomenon of Social Comparison can be caused by social media where social media users tend to compare themselves with other individuals. This affects the Self Confidence of the community. Therefore, this study analyzes the Self Confidence of a person who experiences the phenomenon of Social Comparison. This research uses the theory of New Media Theory, Social Comparison and Self Confidence. This research uses qualitative methods with a phenomenological approach. The subject of the study itself was an Instagram user who experienced Social Comparison. The subjects of this study were Instagram users who experienced the phenomenon of Social Comparison. The results of this study show that a person who experiences the phenomenon of Social Comparison has an impact on decreasing Self Confidence but on the other hand, a positive mindset is formed, namely motivation which increases a person's Self Confidence.